Proceedings of the 2014 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2014
DOI: 10.3115/v1/d14-1156
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging Effective Query Modeling Techniques for Speech Recognition and Summarization

Abstract: Statistical language modeling (LM) that purports to quantify the acceptability of a given piece of text has long been an interesting yet challenging research area. In particular, language modeling for information retrieval (IR) has enjoyed remarkable empirical success; one emerging stream of the LM approach for IR is to employ the pseudo-relevance feedback process to enhance the representation of an input query so as to improve retrieval effectiveness. This paper presents a continuation of such a general line … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Although Chen et al have summarized RM and MMF in the mixture multinomial distribution [12], they have not shown that both RM and MMF comply with the linear combination assumption. With the proof in Appendix A.3, we demonstrate Proposition 5, which shows that MMF complies with the linear combination assumption.…”
Section: Dsm and Mixture Multinomial Distribution Frameworkmentioning
confidence: 99%
See 3 more Smart Citations
“…Although Chen et al have summarized RM and MMF in the mixture multinomial distribution [12], they have not shown that both RM and MMF comply with the linear combination assumption. With the proof in Appendix A.3, we demonstrate Proposition 5, which shows that MMF complies with the linear combination assumption.…”
Section: Dsm and Mixture Multinomial Distribution Frameworkmentioning
confidence: 99%
“…In this section, we will compare DSM with other related works, including mixture model feedback (MMF) [7], fast mixture model feedback (FMMF) [10], regularized mixture model feedback (RMMF) [11], as well as a mixture multinomial distribution framework and a query-specific mixture modelling feedback (QMMF) approach [12]. Since the above models are implemented on two basic relevance feedback models, i.e., relevance model (RM) and mixture model feedback (MMF), we will also compare RM (we use RM to denote RM1 in [2]) and MMF.…”
Section: Comparisons Between Dsm and Related Modelsmentioning
confidence: 99%
See 2 more Smart Citations